The German Wind Energy Lobby: How to successfully promote costly technological change - Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2004)
German wind power development is a technological success story but has involved very high subsidies. Germany was a latecomer in wind power but specific political conditions in the late 1980s and early 1990s allowed the implementation of the feed in tariff regime which has characterised Germany ever since. The wind lobby managed to constitute itself at an early stage and to develop stable alliances with farmers and regional policymakers. The concentration of the wind industry in structurally weak regions reinforced these links. With an increased visibility of the subsidies and saturation of onshore sites in the early 2000s, the lobby has been less successful in retaining support. The current attempt to develop offshore projects may suffer from less favourable interest constellations.
Keywords: Q42; Q58; Q52; 330; Wind power; interest groups; technological change; Windenergie; Windkraftanlage; Interessenpolitik; Förderung regenerativer Energien; Subvention; Erfolgsfaktor; Deutschland